Pengembangan Modul Berbasis Peta Pikiran (Mind Map) untuk Pembelajaran Menulis - Lova Lovenia (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2020)
This study aims to describe the process of developing a mind map-based module that is valid, practical, and effective for learning to write text on observation reports of class X SMA students. This type of research is research and development (R&D). In this case, the writer designed a product in the form of a mind map-based module, especially in the material of writing a valid, practical, and effective observation report text on the observation results of class X SMA students. The development model used is the 4-D model which consists of four development stages, namely definition, design, development, and distribution. To determine the validity, practicality, and effectiveness of the modules that have been made, the data were analyzed using descriptive statistics which are used to analyze the data by describing or describing the collected data as it is. In this study it was found that the mind map-based module for learning to write a text on the observation report developed can be declared valid (seen from the point of view of content, presentation, language, and graphics), practical (in terms of ease of use and compatibility with time), and effective (seen from the activities, attitudes, and student learning outcomes). The use of designed modules has direct implications in the learning process because the material presented is the demand of the applicable curriculum. Therefore, using modules can make it easier for students to understand and master the material. Besides, the role of the teacher as a facilitator will be realized because of the availability of learning resources with complete explanations and attractive presentations. It aims to facilitate teachers in the learning process.